Magic and divination in Malay illustrated manuscripts - Yahya, Farouk. (Arts and Archaeology of the Islamic World, 2016)
This book offers an integrated study of the texts and images of illustrated Malay manuscripts on magic and divination from private and public collections in Malaysia, the UK and Indonesia. Containing some of the rare examples of Malay painting, these manuscripts provide direct evidence for the intercultural connections between the Malay region, other parts of Southeast Asia and the rest of the world. In this richly illustrated volume many images and texts are gathered for the first time, making this book essential reading for all those interested in the practice of magic and divination, and the history of Malay, Southeast Asian and Islamic manuscript art.